EFFECT OF DIFFERENT COMPACTION PRESSURE AND DIFFERENT SINTERING ROUTE ON K0.5Na0.5NBO₃ PHYSICAL AND DIELECTRIC PROPERTIES - Bahanurddin, Nor Fatin Khairah; Ahmad, Zainal Arifin; Mohamed, Julie Juliewatty (University of Chemistry and Technology, Prague & Institute of Rock Structure and Mechanics of the ASCR, v.v.i., 2016)
Alkaline niobate known as K0.5Na0.5NbO3 (KNN), a lead-free piezoelectric ceramic was synthesized via a solid state reaction method. The samples were compacted at different pressures (100, 200, 300 and 400 MPa) and sintered using two different techniques (conventional furnace and hot isostatic pressing (HIP)). The effect of compaction pressure and sintering technique on physical and dielectric properties was studied. The optimum compaction pressure (300 MPa) and sintering via HIP (at 1080°C for 30 min) increased the density and grain size (range 30 - 300 nm) and improved its dielectric properties. Therefore, the combination of suitable compaction pressure and sintering technique has produced larger grain size and higher density of KNN which resulted in outstanding dielectric properties. At room temperature, excellent values of ɛr (5517.35) and tan δ (0.954), recorded at 1 MHz were measured for the KNN300HIP sample with highest density (4.4885 g∙cm-3).